Identification of cassava germplasms resistant to two-spotted spider mite in China: From greenhouse large-scale screening to field validation - Liang, Xiao; Chen, Qing; Liu, Ying; Wu, Chunling; Li, Kaimian; Wu, Mufeng; Yao, Xiaowen; Qiao, Yang; Zhang, Yao; Geng, Yue (Frontiers in Plant Science, 2022)
Utilization of resistant germplasm is considered as an effective, economical and eco-friendly strategy for cassava pest management. Tetranychus urticae, known as the two-spotted spider mite (TSSM), is a devastating pest in Asian cassava planting countries as well as in China. However, the resistant levels of abundant cassava germplasms to TSSM remains largely unknown. To fill this knowledge gap, we conducted screening of 202 cassava germplasm for resistance to TSSM in China, under both greenhouse and field conditions. Based on the classification of mite damage phenotype, the three rounds of large-scale greenhouse experiments had identified two highly resistant (HR) varieties (C1115 and MIANDIAN), five resistant (R) varieties (SC5, SC9, SC15, COLUMBIA-4D and LIMIN) and five highly susceptible (HS) varieties (KU50, BREAD, SC205, TMS60444 and BRA900), besides, these ‘HR’ and ‘R’ varieties would significantly repress the normal development and reproduction of TSSM. In addition, the 12 cassava varieties selected from the greenhouse screening were further subjected to consecutive five years of field validation at Danzhou, Wuming and Baoshan. The seven resistant varieties not only exhibited stable TSSM-resistance performance across the three field environments, but also possessed the same resistant levels as the greenhouse identification, while the resistant varieties SC5 was an exception, which was identified as moderate resistant in Baoshan, indicating the variety-environment interaction may affect its resistance. Furthermore, regional yield estimation suggested that the higher the resistance level was, the better capacity in reducing the yield losses. This study demonstrated that the TSSM-resistant varieties could be considered as ideal materials in mite control or in future breeding programme of mite-resistant cassava plant.